Risk of ischemic stroke in patients with polymyositis and dermatomyositis: a systematic review and meta-analysis - Patompong Ungprasert (2018)
© 2014, Springer-Verlag Berlin Heidelberg. Several chronic inflammatory disorders, such as rheumatoid arthritis and systemic lupus erythematosus, have been demonstrated to increase ischemic stroke risk, but the data on polymyositis (PM) and dermatomyositis (DM) remain unclear. We conducted a systematic review and meta-analysis of observational studies that reported odds ratio, relative risk, hazard ratio or standardized incidence ratio comparing ischemic risk in patients with PM/DM versus non-PM/DM participants. Pooled risk ratio and 95 % confidence intervals were calculated using a random-effect, generic inverse variance method of DerSimonian and Laird. Three cohort studies were identified and included in our data analysis. The pooled risk ratio of ischemic stroke in patients with PM/DM was 1.61 (95 % CI 1.28–2.02). The statistical heterogeneity of this meta-analysis was insignificant with an I < sup > 2 < /sup > of 0 %. Our study demonstrated a statistically significant increased ischemic stroke risk among patients with PM/DM.